(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This thesis investigates the strategic implementation of halal standards within the hospitality sector, specifically in hotel operations. With the global rise of Muslim travelers seeking faith-aligned services, the paper outlines the extensive scope of halal compliance beyond dietary restrictions to include hygiene, privacy, ethical behavior, and religious accommodations. The study emphasizes that adopting halal standards can serve as a competitive advantage for hotels, offering market differentiation, cultural inclusivity, and ethical branding. It also explores the role of halal certification in building consumer trust and presents a critical analysis of the operational opportunities and challenges involved. The work provides a roadmap for hoteliers aiming to enter or expand within the halal tourism market, highlighting the business, social, and cultural benefits of aligning with Islamic principles